Paleofire reconstruction based on an ensemble‐member strategy applied to sedimentary charcoal. Issue 11 (7th June 2013) - Blarquez, Olivier; Girardin, Martin P.; Leys, Bérangère; Ali, Adam A.; Aleman, Julie C.; Bergeron, Yves; Carcaillet, Christopher
Abstract: [1] Paleofire events obtained from the statistical treatment of sedimentary charcoal records rely on a number of assumptions and user's choices, increasing the uncertainty of reconstructio s. Among the assumptions made when analyzing charcoal series is the choice of a filtering method for raw Charcoal Accumulation Rate (CHARraw ). As there is no ultimate CHARraw filtering method, we propose an ensemble‐member approach to reconstruct fire events. We modified the commonly used procedure by including a routine replicating the analysis of a charcoal record using custom smoothing parameters. Dates of robust fire events, uncertainties in fire‐return intervals and fire frequencies are derived from members' distributions. An application of the method is used to quantify uncertainties due to data treatment in two CHARraw sequences from two different biomes, subalpine and boreal. Key Points: Our innovative approach enables to determine robust fire event dates We assessed paleofire frequency using ensemble member's reconstructions